Achieving Efficient Solution‐Processed Blue Narrowband Emitting OLEDs with Small Efficiency Roll‐Off by Using a Bulky TADF Sensitizer with High Reverse Intersystem Crossing Rate. Issue 2 (1st December 2022) - Chen, Liang; Chang, Yufei; Shu, Haiyang; Li, Qiang; Shi, Song; Wang, Shumeng; Wang, Lixiang
Abstract: Solution‐processed organic light‐emitting diodes (OLEDs) based on multiple‐resonance thermally activated delayed fluorescence (MR‐TADF) emitters exhibit high color purity for next‐generation ultrahigh‐definition display. However, they suffer from low efficiency and large efficiency roll‐off due to slow triplet exciton upconversion of MR‐TADF emitters, resulting in serious triplet exciton quenching. Here, efficient solution‐processed blue MR‐TADF OLEDs featured with small efficiency roll‐off are developed by using a new bulky TADF sensitizer consisting of five di‐tert‐butylcarbazoles and one triazine with high reverse intersystem crossing rate of 2.0 × 10 7 s −1, which can rapidly convert triplet excitons to singlet ones to avoid exciton quenching. The Dexter energy transfer from the sensitizer to the MR‐TADF emitter is blocked by using tertiary butyl groups as the bulky unit in the sensitizer to increase the intermolecular distance for ensuring fast upconversion of triplet excitons on the sensitizer. And then the singlet excitons on sensitizer transfer to the emitter through long‐range Förster resonance energy transfer for narrowband emission. As a result, a maximum external quantum efficiency of 23.9% is achieved for the sensitized devices, slightly declining to 21.5% at a practical luminance of 1000 cd m −2 . To the best of the authors' knowledge, this is the best result for solution‐processed blue MR‐TADF OLEDs. Abstract : Efficient solution‐processed blue narrowband organic light‐emitting diodes with small efficiency roll‐off are developed by using a new bulky thermally activated delayed fluorescence sensitizer with high reverse intersystem crossing rate and precisely controlling energy transfer. High external quantum efficiency of 23.9% is achieved, which slightly decreases to 21.5% at 1000 cd m −2 with small efficiency roll‐off of only 10.0%.